Struktur Internal Organ Reproduksi Tumbuhan Berbiji (Angiospermae dan Gymnospermae) - Agnie Airul Akira; Alvi Arumi Fadila; Aprilia Khoirunnisa Emnur; Fida Qurrotul Aini; Gina Satira; Ita Fitriyyah (Mikroba : Jurnal Ilmu Tanaman, Sains Dan Teknologi Pertanian, 2024)
Open seed plants or Gymnosperms and closed seed plants or Angiosperms are two subdivisions of seed plants. Seed plants reproduction tool consists of strobilus or flowers. The reproductive tool of closed seed plants is a flower that grows from a bud equipped with petals, stamens, and pistils. The purpose of this study was to observe the reproductive structure of seed plants. This research was conducted at Instructional Laboratory 1, UIN Sunan Gunung Djati Bandung. The method used was direct observation in the laboratory by analyzing the internal structure of reproductive organs. The results Angiosperms such as bungur flowers (Lagerstroemia speciosa) have complete reproductive organs and produce seeds in closed ovaries, while gymnosperms such as pine (Pinus merkusii) have strobilus as reproductive organs and open seeds. Although gymnosperms and angiosperms share many similarities in basic adaptations and functions, they differ significantly in internal structure and reproductive mechanisms.